2007
DOI: 10.1007/s00417-006-0531-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of amino acids and glutamate transport in the DBA/2J mouse retina; possible clues to degeneration

Abstract: Alterations of amino acid content and enhanced glutamate neurotransmission might be involved in the pathogenesis of retinal neurodegeneration in the DBA/ 2J mouse model of ocular hypertension. Moreover, these mice provide an animal model for studying excitotoxic retinal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
(61 reference statements)
4
21
0
Order By: Relevance
“…Changes of retinal and/or intravitreal amino acid concentrations in experimental models of ocular hypertension are widely debated. Recently, however, alterations of the amino acid metabolism (mainly of glutamate) were reported to be involved in experimental ocular hypertension [8][9][10]. Although an altered membrane physiology of Müller cells from patients with secondary glaucoma has been demonstrated [11], there is no detailed study of the respective parameters in any animal model of ocular hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…Changes of retinal and/or intravitreal amino acid concentrations in experimental models of ocular hypertension are widely debated. Recently, however, alterations of the amino acid metabolism (mainly of glutamate) were reported to be involved in experimental ocular hypertension [8][9][10]. Although an altered membrane physiology of Müller cells from patients with secondary glaucoma has been demonstrated [11], there is no detailed study of the respective parameters in any animal model of ocular hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, a decrease of GLT-1 was found after trabecular laser treatment [24] and in transgenic mice bearing spontaneous ocular hypertension [26]. Vice versa , GLT-1 was increased in photoreceptors and bipolar cells from eye subjected to episcleral vein cauterization [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of EAATs in retinal injuries, and in particular under retinal ischemia/reperfusion, remains controversial [24]–[26]. Most of the available data are related to the ischemic phase of retinal injury, while less is known on the role of EAATs during the reperfusion phase, which is crucial for the damage propagation and therefore the extent of neuronal death.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that GLAST expression diminishes [55][56][57] or remains stable [58] in experimental glaucoma, whereas others have reported increased expression [59]. Thus, it remains unclear whether elevated intraocular pressure (IOP) alters glutamate uptake by modulating GLAST.…”
Section: Impairment Of Glutamate Removal In Glaucoma a Glastmentioning
confidence: 99%
“…Several studies [56,64] revealed that the expression of the major glutamate transporter, GLAST, decreases after pressure loading. Therefore, agents that effectively enhance glutamate transporter function may serve as potential therapeutics against the pressure-induced injury.…”
Section: Neuroprotection By Upregulation Of Glutamate Transportersmentioning
confidence: 99%